Presença de princípios morinianos (dialógico, recursivo e hologramático) na relação entre educação e Tecnologias Digitais Contemporâneas: um estudo de caso. - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This Master's Dissertation Text entitled Presence of Morinian Principles (Dialogical, Recursive and Hologramatic) in the Relationship Between Education and Contemporary Digital Technologies: a case study presents the research work carried out with the general objective of investigating at theoretical, methodological and technicians the presence and dynamics of dialogical, recursive and hologramatic principles of Morinian complexity theory in the relationship between Education and Contemporary Digital Technologies, through a case study, at the Maria Teixeira School located in the municipality of Luziânia, State of Goiás (GO). We have as specific objectives: to conceptualize and reflect on Education, Contemporary Digital Technologies and the dialogic, recursive and hologramatic principles of Morinian complexity theory; observe and identify the presence of these three principles of the Morinian theory of complexity in the educational practice of the school and its relations with the Contemporary Digital Technologies; contextualize, describe and analyze, together with the teaching and learning process, educational actions implemented in the school, which are verified in the field research, related to the Morinian theory and its three principles. This text was prepared under the theoretical scope of Edgar Morin (2002; 2003; 2005; 2007), as well as the authors: Lévy (1997 and 1999); Lacerda Santos (2011; 2014 and 2018); Libâneo (1992 and 2012); Almeida (2004); and Moreira (2002); between others. It was methodologically developed through qualitative research; in the modality of a case study that used as data collection instruments: semi-structured interviews and document analysis.We verified, in our discussions of the analysis in general, that the principles of the theory of complexity listed in our research are present throughout the school and are participants in the pedagogical actions planned and constant in the PPP, carried out in the educational work and evaluated in the results represented by the philosophy education of unrestricted inclusion in the practice of the traditional motto of the Maria Teixeira School.
Keywords: Ações pedagógicas; Educação; Princípios dialógico, recursivo e hologramático; Tecnologias digitais contemporâneas; Teoria da complexidade; Complexity Theory; Contemporary Digital Technologies; Dialogical, recursive and hologrammatical principles; Education; Pedagogical actions; CIENCIAS HUMANAS::EDUCACAO